PENGARUH PENDIDIKAN FORMAL, MOTIVASI DAN PENDIDIKAN PELATIHAN TERHADAP KINERJA PETUGAS PENGAWAS DI LINGKUNGAN BALAI BESAR WILAYAH SUNGAI BENGAWAN SOLO - Lazim, Mat -; Triyaningsih, Sri Lestari (Universitas Slamet Riyadi, 2013)
This study aims to analyze the significant influence of: (1) the performance of formal education; (2) motivation on performance; and (3) educational training on the performance of the environmental control officers Central River Region Solo. The analysis showed: (1) There is a significant relationship between formal education on performance; (2) There is a significant effect of motivation on performance; (3) There is a significant relationship between education training supervisors on employee performance environment Central River Region Solo; (4) educational training the dominant influence on the environmental performance of officers Central River Region Solo. Conclusion of the study: (1) the hypothesis that there is a significant effect of educational level on the performance of the environmental control officers Central River Region Bengawan Solo verified; (2) the hypothesis that there is a significant effect of motivation on the performance of the environmental control officers Bengawan Central River Region Solo verified; (3) the hypothesis that there is a significant effect of training on the performance of the environmental control officers Central River Region Solo. Education training is a dominant variable influence on the environmental performance of supervisors Central River Region proven true. Keywords: Formal Education, Motivation, Education Training, Performance